Literature Review on The Effect of Economic Intelligence on Economic Growth Improvement With Tax Evasion as Mediating Variable - Celine Tjandra; Palupi Lindiasari Samputra (Journal Research of Social Science, Economics, and Management, 2025)
Taxation is one of the sources of state revenue that greatly affects economic growth. However, major challenges arise due to tax evasion practices carried out by taxpayers illegally, thereby reducing the potential for state revenue. This phenomenon not only has an impact on weakening the country's fiscal capacity, but also hinders the pace of economic growth nationally. Therefore, this study aims to analyze the relationship between tax evasion, economic growth, and economic intelligence. Economic Intelligence is one of the approaches to economic resilience that can be a solution in infrastructure and prevention rather than recovering after tax evasion has occurred. This study uses a systematic literature review approach from previous research taken from summon discovery results found 493 previous studies then after being selected for the last 10 years and found that there are 29 previous studies that are suitable for this topic. The results of this study show that the majority of studies find a negative relationship between tax evasion and economic growth, while an approach based on economic intelligence by integrating technologies such as machine learning, blockchain, and big data analytics has proven to be effective in reducing tax evasion rates.